Aplicação do método de análise hierárquica AHP para a seleção de tecnologias limpas na geração de energia em uma termelétrica a carvão mineral - Oliveira, Andressa Padilha de (2017)
The expansion of energy supply is fundamental for the economic and social development of a country, influencing decisively the infrastructure of the production sectors. Coal is the main source of energy in the world. China, the United States of America and India account for 70% of total fuel consumption. In Brazil, this energy has a smaller share of the domestic energy supply, 5.5% of the total. Despite this, issues of energy security, stable prices and low prices make this option economically attractive considering it a strategic source, with the largest national reserves located in Rio Grande do Sul. The research aims to study the management of clean technologies developed to minimize the emission of atmospheric pollutants from the combustion of coal from a thermoelectric plant in southern Brazil, and to apply the Analytic Hierarchy Process to the hierarchy of viable technological alternatives to the production process. The information acquired, regarding the emerging actions of environmental management processes, involved the application of questionnaire, semi-structured interview, checklist and on-site observation. In addition, we analyzed formal documents, operational database and publications that report the environmental performance of the company in the national market. The paper addressed the direct relationship between the most relevant environmental impacts, which correspond to the air emissions released during the plant's operating period and the technological options adopted in the treatment of gases and wastes of the thermoelectric complex. The application of the Analytic Hierarchy Process has identified the investment in a coal beneficiation plant as the most accessible technology compatible with the production process, which contributes to increase the quality of the fuel. The investment cost was defined as the most important criterion when compared to the implementation time and maintenance cost. In this way, the articulation of effective methods and technologies for the control of emissions and particulates, together with the valorization of the environmental management system, proved to be more adequate to meet environmental demands and optimize the efficiency of the generation plant, converging technical interests, economic and commercial impacts on the reduction of environmental impacts.